Analisis Penghapusbukuan oleh Bank terhadap Utang Debitur atas Kredit Macet - Putri, Leonita Anastasya (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
This study aimed to analyze write-off as a form of settlement over bad credit and the legal consequences of write-off by banks on debtors' debts over bad credit. The study used the normative juridical research method. From the discussion, it was obtained that the write-off was not as a settlement of bad credit between the two parties but rather the settlement of only one party, namely the creditor. The legal consequence of a write-off was that the creditor still had the right to claim the debtor so that the debtor was still obliged to pay to the creditor. Nevertheless, the bank's obligation to pay taxes had not increased.